Analisis Gaya Hambat Sepeda Listrik VU-EV (Vokasi Unesa-Electric Vehicle) Roda Tiga Yang Terintegrasi Panel Surya Menggunakan CFD Dengan Variasi Desain Body - Iqbal Zarkasyi Herianto; Ferly Isnomo Abdi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study is motivated by the increasing demand for sustainable transportation and energy efficiency in three-wheeled electric vehicles. The VU-EV (Vokasi Unesa-Electric Vehicle) was developed with integrated solar panels to improve driving range. The research method used was an experimental approach based on Computational Fluid Dynamics (CFD) simulation using SolidWorks software. This study involved variations in solar panel design and airflow velocities (19, 25, and 35 km/h). The analyzed parameters included drag coefficient (Cd), pressure distribution, and airflow patterns (streamline) to determine the most aerodynamically efficient design. Variations in airflow speed have a significant effect on the flow characteristics and aerodynamic forces of the VU-EV electric bike. At a low speed of 19 km/h the drag force value obtained is 3.251 N and the lift force is 2.43 N. Then at a speed of 25 km/h the drag force value is 5.637 N, while the lift force value is 3.666 N. Then at a speed of 35 km/h the drag force value is 10.970 N, while the lift force value is obtained at 6.557 N. The pressure distribution tends to be even with a small difference, Meanwhile, at higher speeds, there is an increase in pressure at the front due to stagnation points and a decrease in pressure at the rear due to the formation of a clearer wake region, accompanied by an increasingly complex flow pattern with separation and turbulence. As speed increases, drag and lift also increase, suggesting that speed increases not only increase drag but also potentially lower vehicle stability.